Treatment of Medial Canthal Tumor by Rotation Flap: Doi:10.36351/pjo.v36i4.1047 - Qurban, Qirat; Kamil, Zeeshan; Mahmood, Khalid (Pakistan Journal of Ophthalmology, 2020)
Purpose: To describe the cosmetic outcome after repairing medial canthal defects via glabellar rotation flaps in patients undergoing wide clear margin excision of medial canthal tumour. Study Design: Interventional case series. Place and Duration of Study: This study was conducted at Khalid Eye Clinic, Nazimabad, Karachi, from March 2019 to August 2019. Methods: Study approval was obtained from the Ethical Review Committee. Eleven patients of both genders with clinically suspected medial canthal tumor were included in the study. Patients who underwent previous treatment such as radiation, cryotherapy or surgery were excluded. All surgeries were done to remove the tumor along with surrounding wide clear margins followed by reconstruction of the defect of the medial canthusareawith the help of arotation flap. Patients were followed for a period of up to six months post operatively for any wound related problems or recurrence. All patients were informed about the study and consent was obtained from each of them. Results: All eleven patients of this study were satisfied at the end of the follow-up period with the final cosmetic outcome. Seven out of elevenpatients were males and the remaining four were females, which also highlighted a greater incidence of medial canthal tumors in the male gender. Conclusion: Glabellar rotation flap is a suitable procedurefor themedial canthal area restoration after the tumor excision and can be customizedas per the characteristics of the surrounding skin as well as thesite, dimensions, and profundity of the defect. Key Words: Medial canthal tumor, Glabellar rotation flap, Medial canthus.